2016
DOI: 10.3847/2041-8205/818/2/l33
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Brief Optical Flashes Associated With the Seti Target Kic 8462852

Abstract: The F-type star KIC 8462852 has recently been identified as an exceptional target for SETI (search for extraterrestrial intelligence) observations. We describe an analysis methodology for optical SETI, which we have used to analyse nine hours of serendipitous archival observations of KIC 8462852 made with the VERITAS gamma-ray observatory between 2009 and 2015. No evidence of pulsed optical beacons, above a pulse intensity at the Earth of approximately 1 photon m −2 , is found. We also discuss the potential us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…These searches targeted both stars and galaxies, and more recently stars harboring known exoplanets (Siemion et al 2013). Searches for both continuously transmitting and short duration light pulses in the visible spectrum (optical SETI) have been conducted (Wright et al 2001;Reines and Marcy 2002;Howard et al 2004;Stone et al 2005;Howard et al 2007, Hanna et al 2009, Tellis & Marcy 2015, Abeysekara et al 2016. A unique search for near-infrared pulses has also begun (Wright et al 2014c, Maire et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These searches targeted both stars and galaxies, and more recently stars harboring known exoplanets (Siemion et al 2013). Searches for both continuously transmitting and short duration light pulses in the visible spectrum (optical SETI) have been conducted (Wright et al 2001;Reines and Marcy 2002;Howard et al 2004;Stone et al 2005;Howard et al 2007, Hanna et al 2009, Tellis & Marcy 2015, Abeysekara et al 2016. A unique search for near-infrared pulses has also begun (Wright et al 2014c, Maire et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This latter technique was put to the test recently with the strange photometry of KIC 8462852, commonly referred to as Boyajian's Star. This star has been since imaged in the visible, infrared, and radio domains, yielding prospective explanations for its unusual light curve that include breakup of comets near the star, unusual inhomogeneities and pulsations on the stellar surface, passing dust clouds, and consumption of an orbiting planet (Schuetz et al 2015, Marengo et al 2015, Abeysekara et al 2016, Bodman & Quillen 2016, Boyajian et al 2016, Wright et al 2016, Metzger et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the flux from a surface reflecting diffusely and uniformly into the sky (Lambertian reflection) with albedo ρ is: Artifacts would probably be spinning, visible for only a small fraction of the time as the cone of reflected sunlight repeatedly sweeps the Earth. The instantaneous flux may be a useful quantity for some setups with very fast photodetectors, like the Cherenkov telescopes that occasionally see satellite glints (Deil et al 2009;Abeysekara et al 2016). CCD based surveys, though, which make up the majority of large-sky surveys, have exposure times from seconds to minutes.…”
Section: Accurate Flash Duration For Mirrors At Oppositionmentioning
confidence: 99%
“…It found one event, a triplet of flashes that can be explained as glints from a rotating satellite or fragment (Deil et al 2009). Recently, Abeysekara et al (2016) reported the serendipitous discovery of a train of optical pulses crossing the VER-ITAS field of view during optical SETI observations of KIC 8462852, also attributed to a satellite. Far more spectacular than any of these are the Iridium flares, with peak brightnesses exceeding magnitude −7, caused by the reflection of sunlight on the antennas of satellites in the old Iridium constellation (Maley & Pizzicaroli 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Prioritization criteria are currently limited to parameters for life as we know it ( e.g. , exoplanets in the habitable zone of their parent stars; unexplained signals from known exoplanetary systems, see Harp et al , 2015; Schuetz et al , 2015; Abeysekara et al , 2016). Those criteria will be refined over time as universal markers are being identified and as we learn more about possible exotic biochemistries ( e.g.…”
Section: An Integrated Vision Moving Forwardmentioning
confidence: 99%